Oral acyclovir therapy of genital herpes simplex virus type 2 infections in guinea pigs. - Ellis, M N (1985)
Oral acyclovir was evaluated for its effectiveness in treating guinea pigs with primary herpes simplex virus type 2 infections. Guinea pigs inoculated intravaginally with acyclovir-susceptible strains (for which 50% inhibitory concentrations of acyclovir in cell culture were found to be in the range of 0.15 to 1.2 micrograms/ml) and treated with 5.0 mg of acyclovir per ml in the drinking water beginning 48 h postinfection showed significant reductions in lesion severity. This dosage produced serum acyclovir levels of 1.3 micrograms/ml. Lower concentrations of oral acyclovir (less than or equal to 2.5 mg/ml in the drinking water), which produced serum acyclovir levels of less than 1.0 microgram/ml, were less consistently effective against these same virus strains. When an acyclovir-resistant isolate (for which the 50% inhibitory concentration of acyclovir in cell culture was found to be 8.5 micrograms/ml) was used to initiate infection, treatment with 5 or 10 mg/ml (yielding serum levels of 1.3 and 3.5 micrograms/ml) in the drinking water had only minimal clinical benefit. However, the degree of response was difficult to determine because of the attenuated disease produced by the acyclovir-resistant virus. In vitro virus sensitivity may be predictive of the serum drug levels that need to be obtained to produce a successful response to therapy.